The Wests of Texas : Cattle Ranching Entrepreneurs - Shackelford, Bruce M., 1952- (Book collections on Project MUSE., 2015)
Bruce M. Shackelford is a nationally recognized authority on the history of the American West. Currently the Curator of the South Texas Heritage Center and the George West Trail Drivers Gallery at the Witte Museum in San Antonio, Texas, he has created exhibits utilizing the Museum's important history collections on subjects from American Indian cultures to the history of horsemanship and the cattle industry in North America. In addition he frequently lectures on related topics and has written numerous articles, authored chapters for the books Black Cowboys of Texas and Texas Women on the Cattl.